YOSH VA KATTA YOSHLI GIMNASTIKACHILARNING MAXSUS JISMONIY TAYYORGARLIGI - Xaytmetov, I.S.; Abdullayev, B.B.; Toshpoʻlatov, A.A. (SCIENCE and SOCIETY, 2024)
In the process of developing physical qualities at work, in order to master one type of exercise in a timely manner, it is important not only to study movements that are similar in structure, but also to make a technical basis out of them. development of the level of special physical fitness with the help of gymnastic exercises in the preparation of young gymnasts in gymnastics through.
Keywords: training session; physical training; technical training; special physical training; applied gymnastics exercises; coordination ability; strength; endurance; basic gymnastic means; practical skills; theoretical knowledge